Analisis Emisi Gas Rumah Kaca pada Green Procurement Rantai Pasok Program Makan Bergizi Gratis Menggunakan Life Cycle Assessment - Dini Daniarti Djeshepanie; Yayat Yayat; Pebi Yuda Pratama (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The Free Nutritious Meal program involves food procurement activities that may generate emissions from inbound transport and packaging waste. This study evaluates greenhouse gas emissions in green procurement practices at SPPG Padasuka Kutawaringin. A Life Cycle Assessment approach was applied with a system boundary covering inbound transport and non-returnable packaging waste handling. Data were collected through 18 days of observation involving five fresh-food vendors and were assessed using the Global Warming Potential indicator (kg CO2e). The results show total emissions of 8.526 kg CO2e/day, consisting of 0.750 kg CO2e/day from transport (8.8%) and 7.776 kg CO2e/day from packaging (91.2%). The main hotspot was single-use plastic packaging, especially from vegetable supply. The study recommends returnable packaging requirements and environmental clauses in procurement contracts.